2021
DOI: 10.3390/joitmc7030177
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Information-Resource Sharing within the Enterprise: A Perspective of Blockchain Consensus Perception

Abstract: The prevalence of information technology (IT) and information systems (IS) provides opportunities for enterprises to sustain open innovation. However, information silos that appeared with IS use have made IS inconvenient and thus impeded enterprises’ open innovation. The present study, therefore, aims to resolve this issue by helping understand how to encourage information-resource sharing within the enterprise. We first proposed a new concept—consensus perception—based on the blockchain characteristics and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…The authors of [25] concluded that IoT and blockchain integration can produce a higher social economy and greater scientific research value. The authors of [26] use blockchain to realize the data security sharing of internal information, with the closer integration of blockchain and artificial intelligence technology [27]. In the future, new technologies are bound to be produced, combining IoT, blockchain and artificial intelligence.…”
Section: Iot Blockchainmentioning
confidence: 99%
“…The authors of [25] concluded that IoT and blockchain integration can produce a higher social economy and greater scientific research value. The authors of [26] use blockchain to realize the data security sharing of internal information, with the closer integration of blockchain and artificial intelligence technology [27]. In the future, new technologies are bound to be produced, combining IoT, blockchain and artificial intelligence.…”
Section: Iot Blockchainmentioning
confidence: 99%